2002
DOI: 10.1152/ajpcell.00323.2001
|View full text |Cite
|
Sign up to set email alerts
|

ANG II and LPA induce Pyk2 tyrosine phosphorylation in intestinal epithelial cells: role of Ca2+, PKC, and Rho kinase

Abstract: 2001.-The G protein-coupled receptor agonists angiotensin II (ANG II) and lysophosphatidic acid (LPA) rapidly induce tyrosine phosphorylation of the cytosolic proline-rich tyrosine kinase 2 (Pyk2) in IEC-18 intestinal epithelial cells. The combined Pyk2 tyrosine phosphorylation induced by phorbol 12,13-dibutyrate, a direct agonist of protein kinase C (PKC), and ionomycin, a Ca 2ϩ ionophore, was equal to that induced by ANG II. Inhibition of either PKC or Ca 2ϩ signaling attenuated the effect of ANG II and LPA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 67 publications
(150 reference statements)
2
29
1
Order By: Relevance
“…However, our results have similarities and differences from studies investigating the magnitude of stimulation of the different sites in one of the kinases in a given cell. Our results with PYK2 differ from those reported with endothelin-1 in mesangial cells (45), in which all three sites had equal magnitude of phosphorylation, and from a number of cells in which the relative magnitude of stimulation of phosphorylation of the different sites differed from ours (angiotensin or lysophosphatidic acid in mesangial cells (57), histamine in platelets (43), thrombin in HUVEC cells (46), and hepatocyte growth factor in lung cancer cells (44)). Our results with the PYK2 phosphospecific sites were similar to the magnitude of stimulation at each site in HUVEC cells with thrombin (43).…”
Section: Resultscontrasting
confidence: 96%
“…However, our results have similarities and differences from studies investigating the magnitude of stimulation of the different sites in one of the kinases in a given cell. Our results with PYK2 differ from those reported with endothelin-1 in mesangial cells (45), in which all three sites had equal magnitude of phosphorylation, and from a number of cells in which the relative magnitude of stimulation of phosphorylation of the different sites differed from ours (angiotensin or lysophosphatidic acid in mesangial cells (57), histamine in platelets (43), thrombin in HUVEC cells (46), and hepatocyte growth factor in lung cancer cells (44)). Our results with the PYK2 phosphospecific sites were similar to the magnitude of stimulation at each site in HUVEC cells with thrombin (43).…”
Section: Resultscontrasting
confidence: 96%
“…Previous studies from our laboratory demonstrated that ANGII induces a rapid increase in [Ca 2+ ] i in IEC-18 cells [48] and that agonists of Gq-coupled receptors elicit FAK Ser-843 phosphorylation through a Ca 2+ -dependent pathway in Swiss 3T3 fibroblasts [37]. Here, we demonstrate that treatment of IEC-18 cells with the Ca 2+ ionophore ionomycin induced a striking, rapid and transient increase in FAK phosphorylation at Ser-843.…”
Section: Discussionsupporting
confidence: 55%
“…ANG II binds to specific endogenous receptors in intestinal epithelial IEC-18 cells [44] and induces multiple signaling pathways and biological responses in these cells, including DNA synthesis and proliferation [45][46][47][48][49]. As shown by the results presented in Fig.1 A (control), stimulation with ANGII also markedly increased the migration of IEC-18 cells into the denuded area of a razor blade wound.…”
Section: Ang II Induces Fak Phosphorylation At Ser-910 In Iec-18 Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…These cells endogenously express G␣ q/11 -coupled receptors for angiotensin II (ANG II) and vasopressin (23,39,40,(43)(44)(45)(46) and have been extensively used as a model system to examine signal transduction pathways in response to GPCR activation (23,36,38,39,(43)(44)(45)47). ANG II and vasopressin act as potent growth factors for IEC-18 and IEC-6 cells (23,39,(43)(44)(45)47). Because the levels of YAP/TAZ influence their association with transcriptional cofactors especially when expressed at elevated levels, we studied the localization, phosphorylation, and activity of the endogenous YAP protein.…”
Section: Identification Of a Novel Pattern Of Yap Nuclear-cytoplasmicmentioning
confidence: 99%